Long non-coding RNA HOXA-AS3 promotes cell proliferation of oral squamous cell carcinoma through sponging microRNA miR-218-5p - Yue Zhao (Taylor & Francis Group, 2021)
Increasing evidence demonstrated long non-coding RNAs (lncRNAs) play important roles in the occurrence and development of oral squamous cell carcinoma (OSCC). This study aimed to explore the role and molecular mechanism of lncRNA HOXA-AS3 in the progression of OSCC. Here, we found that the expression of lncRNA HOXA-AS3 was upregulated in OSCC tissues and cell lines compared with the para-cancerous tissues and normal human oral keratinocyte (NHOK), respectively. Inhibition of HOXA-AS3 significantly inhibited the proliferation and colony formation of OSCC cells. Further, the luciferase reporter assay showed that HOXA-AS3 was directly bound to miR-218-5p. Moreover, the expression of miR-218-5p was negatively regulated by HOXA-AS3, and miR-218-5p could inhibit the expression of collagen type I alpha1 (COL1A1) and lysophosphatidylcholine acyltransferase 1 (LPCAT1). In addition, silencing miR-218-5p reversed the inhibitory effect of HOXA-AS3 knockdown on the proliferative potential of OSCC cells. In summary, our study illustrated that HOXA-AS3 promoted cancer cell proliferation in OSCC, possibly by sponging miR-218-5p for the first time, which provides a new target or a potential diagnostic biomarker for OSCC.